**Note:- 1) If y = sin(x) ; then dy/dx = cos(x)**

**2) If y = x^n ; then dy/dx = n*x^(n-1) ; where n = constant**

Now,

`y = (x/2) - {sin(2x)/4}`

`dy/dx = y' = (1/2) - {2cos(2x)}/4`

`or, dy/dx = y' = (1/2) - cos(2x)/2`

`or, dy/dx = y' = {1-cos(2x)}/2`

``

**Note:- 1) If y = sin(x) ; then dy/dx = cos(x)**

**2) If y = x^n ; then dy/dx = n*x^(n-1) ; where n = constant**

Now,

`y = (x/2) - {sin(2x)/4}`

`dy/dx = y' = (1/2) - {2cos(2x)}/4`

`or, dy/dx = y' = (1/2) - cos(2x)/2`

`or, dy/dx = y' = {1-cos(2x)}/2`

``